Sarawak State Library Kuching, Sarawak / Annie Syafika Mohamad Jelani - Mohamad Jelani, Annie Syafika (Universiti Teknologi MARA, Sarawak, 2013)
Pustaka Negeri Sarawak is considered as a major information resource centre and as the heart of information services especially for the public and private sectors. It links with libraries, collection and information centres elsewhere in Sarawak and throughout Malaysia. In addition, it also provides a gateway into and from publicly accessible international information centres. It is complex serve as a community centre of knowledge and cultural enlightenment, where Malaysians in Sarawak can not only access a vast store of information, in the form of both printed and electronic media, but also gather for educational and cultural exchanges, programmes and participate in many other regularly conducted activities.